2014
DOI: 10.7287/peerj.preprints.471v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNAs expression profile in CCR6+ regulatory T cells

Abstract: Backgroud: CCR6+ CD4+ regulatory T cells (CCR6+Tregs), a distinct Tregs subset, played an important role in various immune diseases. Recent evidence showed that microRNAs (miRNAs) are vital regulators in the function of immune cells. However, the potential role of miRNAs in the function of CCR6+Tregs remains largely unknown. In this study, we detected the expression profile of miRNAs in CCR6+ Tregs. Materials and Methods: The expression profile of miRNAs as well as genes in CCR6+Tregs or CCR6-Tregs from Balb/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Furthermore, CCR6 + Tregs expressed distinct patterns of miRNAs compared with CCR6 − Tregs did. 29 In the present study, we extended these findings by demonstrating that miR-21 could regulate the proliferation ability of CCR6 + Tregs in tumor sites. Similarly, Garchow et al 16 found that miR-21 could regulate the proliferation of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Furthermore, CCR6 + Tregs expressed distinct patterns of miRNAs compared with CCR6 − Tregs did. 29 In the present study, we extended these findings by demonstrating that miR-21 could regulate the proliferation ability of CCR6 + Tregs in tumor sites. Similarly, Garchow et al 16 found that miR-21 could regulate the proliferation of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 70%
“…27,28 Similarly, our most recent work also showed that CCR6 + Tregs expressed distinct miRNA profile compared with their CCR6 − counterpart. 29 These findings might support the fact that miRNAs played critical roles in the regulation of the distinct subset of Tregs. However, the exact regulation mechanism of distinct miRNAs involved in the biological function of different Treg subsets remains largely unknown.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…CD4 1 T cells are an important subpopulation of T cells which play a central role in innate immune responses, maintaining the balance of anti-inflammatory and proinflammatory responses, promoting activation of antigenpresenting cells (APCs) and B cells as well as promoting the accumulation of immune cells [33][34][35][36][37]. Increasing evidence demonstrates that the distinct miRNA molecule plays a critical regulatory role in the development and function of various immune cells, including CD4 1 T cells, which affect the pathogenesis and development of related clinical diseases [38][39][40][41][42][43][44]. For example, Zeng et al [45] reported that down-regulation of miR-451a affects the activation and proliferation of CD4 1 T cells by targeting the transcription factor myelocytomatosis oncogene (Myc) in dilated cardiomyopathy (DCM) patients, which contribute to the immunopathogenesis of DCM.…”
Section: Discussionmentioning
confidence: 99%